Level and modalities of origin of the small saphenous vein: toward codification of the proximal approach level. - Gaye, M.; Diagne, P. A.; Ndiaye, Aï; Diagne, A. M.; Nazarian, S.; Ndiaye, A. (Surgical & Radiologic Anatomy, 2019)
Purpose: The proximal approach to the small saphenous vein (SSV) must be performed according to precise anatomical landmarks to respect the esthetic profile of venous insufficiency surgery. In this work, we propose the tip of the lateral malleolus and the lateral edge of the calcaneal tendon as palpable landmarks from which to easily identify the situation of this vein. Methods: This was a cadaveric dissection study involving 62 members of fresh and embalmed anatomical subjects. We used a horizontal line passing through the tip of the lateral malleolus and the lateral edge of the calcaneal tendon as reference marks. Once the origin of the SSV as dissected, the distances between the saphenous vein and the landmarks were measured. Results: We found that the small saphenous vein was often unique. The origin of this small saphenous vein projected, on average, to 4.40 cm from the horizontal passing through the tip of the lateral malleolus and 1.2 cm from the lateral edge of the calcaneal tendon. Conclusion: These two measurements constitute the orthogonal coordinates for the situation of the small saphenous vein origin.